Armadilhas impregnadas com Beauveria bassiana (Bals.) Vuill. Visando ao controle de Dermanyssus gallinae (De Geer) (Acari: Dermanyssidae) - Nascimento, Marina Martins (2019)
The red mite D. gallinae stands out as the main ectoparasite of birds in commercial poultry farming and, for being a cryptic species, lives hidden in crevices in aviaries, which they leave overnight to feed on birds. The objective of this study was to evaluate different traps prepared with B. bassiana for the control of the mite. In laboratory, the feasibility of conidia in B. bassianain loofah sponge (LS) Luffa aegyptiacatraps was evaluated over 90 days, which remained above 90% until the 35th day of storage. In the field, the same traps were installed in a commercial farm facility and remained for up to 120 hours, after which the mites were collected by means of recapture traps, after 24 hours. The mortality of D. gallinae in the B. bassianaLS traps was 92.2%, remaining efficient for up to 5 days after installation. Mortality in the recapture traps reached 38%. In a second step, the acaricide activity, adhesiveness and viability of conidia in corrugated cardboard traps were evaluated over time under laboratory conditions. In the field, the same traps were installed in a commercial laying aviary (infection traps), remaining for up to 48 hours, and the mites were then collected by means of recapture traps. It was found that the presence of emulsifiable wax SPLAT™ provided greater adherence of the conidia in the traps, as well as greater viability over three weeks of storage, both at 26° and 32°C, contrary to what was observed for pure fungus. In the field tests, there was no difference between the time the trap remained in the environment and the mortality of the mites caught in the traps, reaching 97.02% in the traps with B. bassiana + SPLAT™ + starch. In the recapture traps, the highest mortality was found at the points where the traps were received with B. bassiana + SPLAT™ + A, being this 25.7%. The results obtained here demonstrate the infection capacity of the fungus in the field and its potential to remain in the environment for the control of D. gallinae.